Resilience and symptoms of depression and anxiety in adolescents: the mediating role of fear of missing out - Annastasia Ediati; Dian V. Sakti Kaloeti; Kurniawan Teguh Martono; Lusi Nur Ardhiani (Current Issues in Personality Psychology)
Background This research aimed to determine the relationship of resilience and symptoms of depression and anxiety in Indonesian adolescents, particularly the degree to which the fear of missing out (FoMO) influenced resilience toward symptoms of depression and anxiety.